Outcomes of COVID‐19 infection in pediatric pulmonary hypertension: A single‐center experience. Issue 12 (10th September 2021) - Morales‐Demori, Raysa; Mallory, George B.; Chartan, Corey; Coleman, Ryan; Ruiz, Fadel; Villafranco, Natalie; Whalen, Elise; Varghese, Nidhy
Abstract: Background: The global COVID‐19 pandemic was particularly concerning for the pediatric pulmonary hypertension (PH) population due to immature immune systems and developmental comorbidities. This study aims to describe a single‐center experience of pediatric PH patients diagnosed with COVID‐19 disease. Methods: A retrospective cohort study of all pediatric patients followed by the PH Center at Texas Children's Hospital diagnosed with COVID‐19 infection from April 2020 to February 2021. Results: We identified 23 patients with a median age of 58 months (interquartile range [IQR]: 25–75th, 21–132 months), 48% being Hispanics. Eight patients (35%) required hospitalization; median length of stay was 6 days (IQR: 25–75th, 5–8 days). Only three of these eight patients required increased respiratory support. Targeted PH therapy was escalated in four patients (two in dual and two in triple therapy). There was one mortality in a patient with failing Fontan physiology. Ninety‐one percent of patients have had post‐COVID outpatient follow‐up, median of 101 days (IQR: 25–75th, 50–159 days) from diagnosis. Of the five patients with 6 min walk test (6MWT) data, three (60%) children walked less distance, median of −12 m (IQR: 25–75th, −12 to +49 m) compared to pre‐COVID testing. Postinfection pulmonary function testing (PFT) was notable for decrease in predicted forced vital capacity (FVC; median −6%, range −11% to +6%) and forced expiratory volume in one second (FEV1; median −14%, range −12% to −18%) in 75% of the patients with PFT data. Conclusion: In our institution, COVID‐19 was found more frequently in Hispanics and associated with low mortality.